Quality of life perceived by chronic haemodialysis patients and family members - (:unkn) unknown (EDTNA-ERCA, 2005)
In this study quality of life perceived by 100 haemodialysis patients with family members' viewpoints on the patients' quality of life was studied. The SF-36 was used as the main measurement tool. According to the findings of the study the quality of life scores, perceived by patients, usually ranged between average and below average. The family members perceived patients' social functioning and functional status in the SF-36 more pessimistically but vitality and well-being in the SF-36 more optimistically, when compared to the patients. In the light of the findings obtained from the study, it is suggested to periodically assess the quality of life of haemodialysis patients considering the viewpoints of family members on the patients' quality of life.
Keywords: Family; Haemodialysis; Quality of life; SF-36